Sistem Informasi Akuntansi Pada Koperasi Universitas Atma Jaya Makassar - Astrid Lestari Tungadi (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2013)
This paper focuses on the design of accounting information systems making in cooperative Universitas Atma Jaya Makassar. Where the current system is currently experiencing a lot of problems due to limited human resources, especially in managing partial phase still use the recording in the books and another part that is still simple to use application. This study uses structured design, program PHP, and MySQL as data storage and DB Designer as an analytical tool. Therefore, this study was conducted with the aim of designing a system that can help the processing of accounting data cooperative savings and loan information Universitas Atma Jaya Makassar and generate accounting reports on the management of savings and loans cooperatives Universitas Atma Jaya Makassar.